2012
DOI: 10.5012/bkcs.2012.33.10.3213
|View full text |Cite
|
Sign up to set email alerts
|

Ni/ZnO-based Adsorbents Supported on Al2O3, SiO2, TiO2, ZrO2: A Comparison for Desulfurization of Model Gasoline by Reactive Adsorption

Abstract: Reactive adsorption desulfurization (RADS) experiments were conducted over a series of commercial metal oxide supports (Al 2 O 3 -, SiO 2 -, TiO 2 -and ZrO 2 -) supported Ni/ZnO adsorbents. The adsorbents were characterized by X-ray diffraction (XRD), temperature programmed reduction (TPR), and Fourier transform infrared spectroscopy (FTIR) in order to find out the influence of specific types of surface chemistry and structural characteristics on the sulfur adsorptive capacity. The desulfurization performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…This may be attributed to the formation of new acid sites resulting from the structural rearrangement during the hydrothermal treatments. Since the Lewis acid sites are beneficial for the adsorption of thiophene bearing lone pair electrons, 65 the higher concentration of Lewis acid sites in TiO 2 modified sample after three cycles of hydrothermal treatment may be partially responsible for the improved RADS performance as compared to the unmodified one 23 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be attributed to the formation of new acid sites resulting from the structural rearrangement during the hydrothermal treatments. Since the Lewis acid sites are beneficial for the adsorption of thiophene bearing lone pair electrons, 65 the higher concentration of Lewis acid sites in TiO 2 modified sample after three cycles of hydrothermal treatment may be partially responsible for the improved RADS performance as compared to the unmodified one 23 …”
Section: Resultsmentioning
confidence: 99%
“…The study on the RADS reaction kinetics of Ni/ZnO based adsorbents revealed that the sulfur diffusion in ZnO was identified as the rate‐determining step after partial sulfidation of ZnO, and the high dispersion of ZnO and NiO particles was favorable for the reaction 20‐22 . To enhance the dispersion of Ni and ZnO, different supports have been introduced into the Ni/ZnO‐based catalysts, such as Al 2 O 3 , ZrO 2 , SiO 2 , zeolites 23‐25 . Among the supports being used, Al 2 O 3 is the most common one because of its intrinsic advantages, such as high surface area, low cost and high chemical/mechanical stabilities, triggering extensive interests in the Ni/ZnO‐Al 2 O 3 adsorbents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S4. As can be seen, all samples exhibit a band at 1450 cm -1 attributed to the 19bν (C-C) vibration of pyridine molecules adsorbed at the Lewis acid site [59,60]. Among all tested adsorbents (see Table S3), sample Ni/ZnO-4h possesses the highest concentration of Lewis acid (1.079 mmol g -1 ) compared with other samples, which partially accounts for its high RADS activity.…”
Section: Ft-ir Analysismentioning
confidence: 89%
“…However, during the production process (reaction of isobutene and methanol), the C4 stream (the main source of isobutene) contains many sulfur compounds, such as DMS (dimethyl sulfide) and DMDS (dimethyl disulfide; approximately 45 ppm in MTBE). , The molecular structures of DMDS and MTBE are illustrated in Scheme . Recently, the desulfurization for MTBE is primarily distillation desulfurization, hydrodesulfurization, and adsorption desulfurization. By comparison, distillation is always accompanied by huge energy consumption, and hydrodesulfurization always requires a harsh operating condition under high temperature and pressure. For deep desulfurization, the adsorption desulfurization has been considered the promising technology due to its mild conditions of atmospheric temperature, low pressure, low energy consumption, and simple operation. , …”
Section: Introductionmentioning
confidence: 99%